Asian freedoms : the idea of freedom in East and Southeast Asia - Reid, Anthony, 1939-; Kelly, David, 1948- (Cambridge ; New York : Cambridge University Press, 1998)
Inspired (and goaded) by Orlando Patterson's theory of freedom as a particularly western outgrowth of classical slavery, this book argues that authentic conceptions of freedom are found throughout the Asian region, where they have emerged in complex ways from local institutions and practices. A prestigious group of contributors explores these adaptations and aternative genealogies of freedom from historical, religious, political and ideological perspectives. This timely book will make an important contribution to our understanding of Asian politics and culture, particularly in the light of the politically sensitive 'Asian values' debate.
Includes bibliographical references and index.
Keywords: Human rights -- Southeast Asia; Human rights -- East Asia; Civil rights -- Southeast Asia; Civil rights -- East Asia; Southeast Asia -- Politics and government; East Asia -- Politics and government